Pengaruh Product Bundling Dan Fitur Shopee Live Streaming Terhadap Minat Beli Customer Pada Produk Somethinc Dalam Perspektif Bisnis Islam - Komala Zurni; Any Eliza; Okta Supriyaningsih (Pusat Riset dan Inovasi Nasional, 2024)
The increasingly rapid development of technology has made people aware of paying attention to and caring for their skin in order to make their appearance more beautiful and attractive. Growth in the market share of the beauty industry from 2010-2023 and in 2022 the Somethinc brand was ranked first in the best-selling products in e-commerce, therefore researchers took a study on Somethinc because they wanted to know why people buy Somethinc products. This research uses quantitative methods. The sample in this study amounted to 99 respondents with data collection techniques in this study using primary and secondary data. Data processing in this research used IBM SPSS version 18.